Colony but not social phenotype or status structures the gut bacteria of a eusocial mammal - Connor R. Fitzpatrick; Ilapreet Toor; Melissa M. Holmes (Behavioral Ecology and Sociobiology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Fifty years of co‐evolution and beyond: integrating co‐evolution from molecules to species - Diego Carmona; Connor R. Fitzpatrick; Marc T. J. Johnson (Molecular Ecology, 2015)
Fifty years after Ehrlich and Raven's seminal paper, the idea of co‐evolution continues to grow as a key concept in our understanding of organic evolution. This concept has not only provided a compelling synthesis between evolutionary biology and community ecology, but has also inspired research that extends beyond its original scope. In this article, we identify unresolved questions about the co‐evolutionary process and advocate for the integration of co‐evolutionary research from molecular to interspecific interactions. We address two basic questions: (i) What is co‐evolution and how common is it? (ii) What is the unit of co‐evolution? Both questions aim to explore the heart of the co‐evolutionary process. Despite the claim that co‐evolution is ubiquitous, we argue that there is in fact little evidence to support the view that reciprocal natural selection and coadaptation are common in nature. We also challenge the traditional view that co‐evolution only occurs between traits of interacting species. Co‐evolution has the potential to explain evolutionary processes and patterns that result from intra‐ and intermolecular biochemical interactions within cells, intergenomic interactions (e.g. nuclear‐cytoplasmic) within species, as well as intergenomic interactions mediated by phenotypic traits between species. Research that bridges across these levels of organization will help to advance our understanding of the importance of the co‐evolutionary processes in shaping the diversity of life on Earth.

The importance of plant genotype and contemporary evolution for terrestrial ecosystem processes - Connor R. Fitzpatrick; Anurag A. Agrawal; Nathan Basiliko; Amy P. Hastings; Marney E. Isaac; Michael Preston; Marc T. J. Johnson (Ecology, 2015)
Plant genetic variation and evolutionary dynamics are predicted to impact ecosystem processes but these effects are poorly understood. Here we test the hypothesis that plant genotype and contemporary evolution influence the flux of energy and nutrients through soil, which then feedback to affect seedling performance in subsequent generations. We conducted a multiyear field evolution experiment using the native biennial plant Oenothera biennis . This experiment was coupled with experimental assays to address our hypothesis and quantify the relative importance of evolutionary and ecological factors on multiple ecosystem processes. Plant genotype, contemporary evolution, spatial variation, and herbivory affected ecosystem processes (e.g., leaf decay, soil respiration, seedling performance, N cycling), but their relative importance varied between specific ecosystem variables. Insect herbivory and evolution also contributed to a feedback that affected seedling biomass of O. biennis in the next generation. Our results show that heritable variation among plant genotypes can be an important factor affecting local ecosystem processes, and while effects of contemporary evolution were detectable and sometimes strong, they were often contingent on other ecological factors.

Novel titanocene anti-cancer drugs and their effect on apoptosis and the apoptotic pathway in prostate cancer cells - K. O'Connor; C. Gill; M. Tacke; F.-J. K. Rehmann; K. Strohfeldt; N. Sweeney; J. M. Fitzpatrick; R. W. G. Watson (Apoptosis, 2006)